PARADIGMA MAQASID SHARIAH KONTEMPORER TENTANG SANKSI HUKUM KEBIRI BAGI PELAKU KEJAHATAN PEDOFILIA - Athoillah Islamy; Abdul Aziz Harahap (Jurnal AL-MAQASID: Jurnal Ilmu Kesyariahan dan Keperdataan, 2021)
This study aims to present a contemporary maqasid shariah perspective on the pros and cons of the polemic of the implementation of castration law for perpetrators of pedophilia crimes. This research is a qualitative research in the form of literature review. This type of Islamic law research is included in the category of philosophical normative Islamic law research with a maqasid shariah approach developed by a contemporary Islamic law expert, namely Jasser Auda. The results of the study conclude that the application of legal sanctions of castration for perpetrators of pedophilia crimes does not contradict the perspective of contemporary maqasid sharia. Such a conclusion can be seen from the following three aspects. First, the implementation of the legal sanction of kebir is parallel to the orientation of Islamic law (maqasid shariah) regarding the components contained in the development of the scope of the hifz din concept, including shari'a (law), aqidah (theology) and akhlak (moral ethics). Second, the implementation of legal sanctions for castration for perpetrators of pedophilic crimes does not conflict with the maqasid perspective in the form of mental protection (hifz al-nafs), intellectual protection (hifz al-Aql) and protection of offspring (hifz al-nasl)which are closely related to the physical and psychological conditions experienced by victims. pedophilia is in line with efforts to protect the economy (hifz mal) for victims who have suffered material losses in the recovery process.